2006
DOI: 10.1177/1099800405283567
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Response Rate Variability in Physically Abused Women of Childbearing Age

Abstract: Physical abuse directly affects maternal and fetal/infant health, with documented reports of higher rates of pregnancy termination, neonatal death, and lower birth weights. Although the Centers for Disease Control and Prevention recommend repeated interviews of women of childbearing age to screen for abuse, the paper-and-pencil instruments available for such screening are adversely affected by the hesitancy of women to disclose physical abuse. Biophysical measures of physiological stress adaptations may hold p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…The physiological measures of both mothers and newborns also did not match theoretical predictions and extreme changes noted in prior studies in the same geographic area (Rice & Records, 2006). The results reflected smaller effect sizes than anticipated.…”
Section: Sample Impactcontrasting
confidence: 78%
See 1 more Smart Citation
“…The physiological measures of both mothers and newborns also did not match theoretical predictions and extreme changes noted in prior studies in the same geographic area (Rice & Records, 2006). The results reflected smaller effect sizes than anticipated.…”
Section: Sample Impactcontrasting
confidence: 78%
“…Analysis of the data also indicated that the theoretically predicted effect sizes were at odds with earlier studies on the same population. Prior studies with the same target population in the same geographical area had demonstrated that stress reactivity resulted in significant changes in physiological parameters because of shifts from sympathetic to parasympathetic regulation (Rice & Records, 2006). The disparity of the findings led to an examination of the characteristics of the sample population.…”
Section: Resultsmentioning
confidence: 99%
“…In women, early life adversity is associated with persistent changes in stress reactivity in the autonomic and HPA regulatory systems (Heim et al, 2000;Shea et al, 2005), including altered cortisol parameters (Jogems-Kosterman et al, 2007) and more variable vasovagal heart rate responses (Rice & Records, 2006). Authors of a meta-analysis found significant effects of early life adversity on the cortisol response to social stress, observing that these effects reach a peak in adulthood and are more pronounced in women (Bunea et al, 2017) Pregnancy is also associated with regulatory changes in the HPA axis.…”
mentioning
confidence: 99%
“…Scientific findings have indicated that the integration of biological variables into inquiry will help provide a comprehensive, in-depth picture of phenomena under investigation. Work by Rice and Records (2006) in this issue of Biological Research for Nursing (BRN) serves as an excellent example of the value of biological markers in elucidating complex phenomena. Biophysical measures are likely to provide a more exhaustive means of describing the human experience of stress adaptation than are other approaches alone.…”
mentioning
confidence: 99%